PENGARUH KREDIBILITAS ENDORSER DAN KREATIVITAS IKLAN TERHADAP MINAT BELI DAN KEPUTUSAN PEMBELIAN YAMAHA JUPITER MX DI KOTA PEKANBARU - Andi Fedrawan; Zulkarnain Zulkarnain; Taufiqurrahman Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aimed to analysze Endorser Credibility, Add Creativity on Purchase Intention and Buying Decision, research applied on consumer Yamaha Jupiter MX in Pekanbaru City.This research consists of four variables: the dependent variable, one intervening variable and two independent variables. They are Buying decision (Y2), Purchase Intention (Y1), Add Creativity (X2), and Endorser Credibility (X1). This research was conducted using a sample of 140 people. This research used purposive sampling, based on respondents who pass the criteria to fill in the questionnaire. In terms of data analysis, this research used path analysis method using SPSS (Statistical Package for Social Science) version 20. Based on the hypothesis test conducted, research shows that Endorser Credibility, Add Creativity significant positive effect on Purchase Intention. Endorser Credibility, Add creativity and Purchase Intention have significant positive effect on Buying Decision. Endorser Credibility and Add Creativity Influence buying decisions are moderated by Purchase Intention.Keyword : Endorser Credibility, Add Creativity, Purchase Intention, Buying Decesion.